Treatment modalities and outcome of the renal victims of the Marmara earthquake - KOÇ, MEHMET (KARGER, 2002)
Background/Aims: Treatment of renal problems during natural catastrophes is highly complicated both for medical and logistic reasons. The therapeutic interventions applied to and the outcome of 639 victims with acute renal problems during the catastrophic Marmara earthquake have been the subject of this study. Methods: Questionnaires regarding information about 63 clinical and laboratory variables were sent to 35 reference hospitals that treated the victims. Information considering therapeutic interventions and outcome obtained through these questionnaires was submitted to analysis. Results: At least one form of renal replacement therapy was administered to 477 (74.6%) of the 639 victims. Of these, 437, 11, and 4 were treated solely by intermittent hemodialysis, continuous renal replacement therapy, and peritoneal dialysis, respectively; 25 victims needed more than one dialysis modality. In total, 5,137 hemodialysis sessions were performed. Also, 2,981, 2,837 and 2,594 units of blood, fresh frozen plasma, and human albumin were administered, respectively. Transfusion of these products was usually associated with higher rates of dialysis needs and mortality. Ninety-seven patients (15.2%) died. The mortality rate of dialyzed victims was higher as compared to nondialyzed ones (17.2 vs. 9.3%, p = 0.015). Conclusions: Massive amounts of dialysis treatment as well as blood and blood product transfusions can be necessary in the treatment of catastrophic earthquake victims with nephrological problems. Despite the potential risk of a high mortality, in the case of appropriate and energetic medical interventions, reasonable final outcomes can be achieved. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: Marmara earthquake; crush syndrome; dialysis; outcome; HANSHIN-AWAJI-EARTHQUAKE; CRUSH-SYNDROME; TRAUMATIC RHABDOMYOLYSIS; FAILURE; MANAGEMENT; HEMOFILTRATION; DISASTERS; DIALYSIS; SHOCK